Sustainability of the Sumedang Larang Palace as a Tourism Attraction of the Kingdom of Sunda Heritage in West Java - INGKADIJAYA, Rahmat; ASMANIATI, Fetty; RATNANINGTYAS, Heny; RAHMANITA, Myrza (Journal of Environmental Management and Tourism; Vol 15 No 1 (2024): JEMT, Volume XV, Issue 1(73), Spring 2024DO - 10.14505/jemt.v15.1(73).07, 2024)
Sumedang Larang Palace is the last Sunda Kingdom Palace in West Java today. This study aims to explore the supporting elements of the Sumedang Larang Palace as a tourist attraction for the Sunda Kingdom heritage in West Java. This type of research is descriptive qualitative research. The place of this research is the Sumedang Larang Royal Palace, located in the city of Sumedang. The primary data used in this study were obtained by interview, observation, and documentation. The results showed that the Nazir Waqf Foundation of Sumedang Prince mandated the Sumedang Larang Palace. In managing the Palace as a heritage tourism destination, it has been regulated in the organizational structure of the Foundation. Employee management is carried out by human resource management, who records, directs, supervises, and performs operations. Furthermore, through its management, the Foundation also maintains and adequately manages the collection of historical artifacts of the Sumedang Kingdom at the Geusan Ulun Museum. Resources are collected independently by managing palace assets. The Foundation also cooperates with external parties to organize and manage the Palace by involving the government, academia, the private sector, and the media.